2015
DOI: 10.1134/s1070427215080236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combinations of antimony trioxide with nontoxic flame retardants on the flame resistance and properties of vulcanized rubber based on general-purpose rubbers

Abstract: The possibility of partial replacement of antimony trioxide by nontoxic fl ame retardants (Cloisite 15A organoclay, microquartz, Cloisite 15A + microquartz and aluminum hydroxide + barium borate combinations) was examined for vulcanized rubber based on general-purpose isoprene (SKI-3) and butadiene (SKD) rubbers. The rheometric, physicomechanical, and thermal properties and the fl ame resistance of vulcanized rubber samples containing various fl ame retardants were studied. Combination of antimony trioxide wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It is known [2] that the fire retardant properties of a fire retardant depend on their thermal stability and reactions of their transformation that occur with heat absorption. Therefore, in order to find the most effective fire-retardant systems, the features of the behavior of fire retardants and their combinations when exposed to high temperatures have been studied [3][4][5]. As a result of testing samples by the UL-94 method, it can be concluded that the unmodified sample performed the worst.…”
Section: Experiments 1 the Study Of The Modified Epoxy Resinmentioning
confidence: 99%
“…It is known [2] that the fire retardant properties of a fire retardant depend on their thermal stability and reactions of their transformation that occur with heat absorption. Therefore, in order to find the most effective fire-retardant systems, the features of the behavior of fire retardants and their combinations when exposed to high temperatures have been studied [3][4][5]. As a result of testing samples by the UL-94 method, it can be concluded that the unmodified sample performed the worst.…”
Section: Experiments 1 the Study Of The Modified Epoxy Resinmentioning
confidence: 99%
“…In addition, antimony trioxide is a toxic substance (hazard class 2) [8]. Therefore, it is relevant to completely or partially replace antimony trioxide in fire-resistant polymeric materials with a less harmless and safe compound of mineral origin [9]. In this regard, the purpose of this work is to find an effective additive to replace antimony trioxide in the formulation of PVC cable plastic compound, while retaining the main fire-resistant, thermal, and physical-mechanical characteristics of the cable compound.…”
Section: Introductionmentioning
confidence: 99%